(untitled) (Contemporary Journal of Social Science Review, 2025)
Women Entrepreneurship in driving school is a hard subject to deal with Pakistan because the societal trends restrict the role of women in house hold. This is one of the reasons of the women less prefer to join driving schools however, they are lots of opportunities with challenges by getting proper training in driving school. This study is conducted to find out the possible challenges and opportunities for female entrepreneurs in Pakistan. The data has been collected by interviews. Convenience sampling techniques have been used to select the sample for the study. The result shows that every age group has opportunities to continue the business, but in case of marital status, challenges are more to continue the business. On the other hand, educated female entrepreneurs, mostly are facing challenges to continue the business except diploma and small business courses holders.